Investigation and analysis of personality characteristics of primary palmar hyperhidrosis patients: a cross-sectional observational study - Xiaoyu Wang; Shushi Meng; Yuqing Huang; Jun Chen (European Journal of Medical Research)
Abstract Background Patients with primary palmar hyperhidrosis (PPH) may exhibit distinct personality traits that influence their perception of the condition. These traits can manifest as heightened sensitivity to physical symptoms, as well as feelings of anxiety or depression, especially in social settings. Methods This study is a retrospective cross-sectional observational study aimed to evaluate and analyze the personality characteristics of patients with primary palmar hyperhidrosis using the Personality Diagnostic Questionnaire—Version 4 (PDQ-4). This study explored the relationships between personality traits and various factors, including age, gender, body mass index (BMI), onset age, the age when symptoms began to impact daily life (Impact age), the choice of thoracic sympathectomy nerve segment, and postoperative satisfaction. The study enrolled primary palmar hyperhidrosis patients treated at the Thoracic Surgery Department of Beijing Haidian Hospital between 2016 and 2021, with a total of 791 patients meeting the inclusion criteria. Statistical analyses, such as the Chi-square test and Mann–Whitney U-test, were conducted using SPSS 26.0 to investigate associations between personality traits and various variables. Results Primary palmar hyperhidrosis patients exhibited a higher prevalence of personality disorders at 16.18% compared to the general population, which ranges from 6.1 to 9.5%. Male patients exhibited a statistically significantly higher prevalence of schizoid, narcissistic, and antisocial personality disorders compared to female patients (P < 0.05). Furthermore, postoperative satisfaction among patients with primary palmar hyperhidrosis declined over time, with a statistically significant difference (P < 0.05). Notably, primary palmar hyperhidrosis patient comorbid personality disorders experienced a more pronounced decline in satisfaction. Conclusions Patients with primary palmar hyperhidrosis demonstrate a relatively high prevalence of personality disorders.